ANALYSIS OF THE INFLUENCE OF STAR DELTA SYSTEM IN REDUCE ELECTRIC STARTING SURGE IN 3 PHASE MOTORS - Linkha Hardine; Dian Budhi Santoso; Ridwan Satrio Hadikusuma (Electrician : Jurnal Rekayasa dan Teknologi Elektro, 2022)
Operations in the industry today use induction motors. There are several types of induction motors, one of which is a 3-phase induction motor. In the use of a 3-phase induction motor, there are several problems at the beginning, one of which is that there is a current surge in the starting received by the windings or rotor of a 3-phase induction motor which will cause damage to the motor windings. In previous research, research has been carried out to reduce electric starting spikes in 3 phase motors by lowering the frequency in a study entitled "Adjusting the Speed ​​of a 3 Phase Induction Motor by Changing the Frequency Using the ALTIVAR 12P Inverter" it was found that the frequency of the regulated voltage was low and stable to minimize inrush current in 3-phase motor starting. Therefore, research was conducted on a system that can reduce these problems, namely the use of a star-delta system on a 3-phase motor to reduce electrical starting spikes in a 3-phase motor. In this study, the electric current value was 0.59 A, the star-circuit voltage value was 219.65 V, and the short-circuit current value was 1.01 A.